Risk factors related to COVID-19. Turcios Lima Polyclinic. Pinar del Rio, 2020-2021 - Jorge Félix Rodríguez Ramos; Gema Chávez Ivizate; Raquel Piloto González (Medisur)
Background: timely recognition of certain risk factors helps to identify COVID-19 infection at an early stage, which, together with interdisciplinary and intersectoral participation, allows for the implementation of better strategies and reduction of morbidity and mortality. Objective: to determine the risk factors related to the appearance of COVID-19. Methods: a case-control study was carried out, which included patients treated at the Turcios Lima Community Polyclinic, in Pinar del Río, from 2020 to 2021. The sample selection was random 3:6 (3000 positive cases of COVID-19/6000 controls without the disease), matched by age and sex. Statistical analysis was based on a multivariate strategy, calculation of the Odds Ratio (OR) with 95% confidence intervals (95% CI), and the Chi Square test, with a statistical significance level of p<0.05. Results: the most frequent risk factors were: male sex (X2=8.5900; p<0.001), urban residence (X2=509.03; p<0.001) and occupation as a student or worker (X2=199 .93, p<0.001); as well as personal medical history of diabetes mellitus, arterial hypertension, ischemic heart disease, bronchial asthma, heart failure, and chronic obstructive pulmonary disease. Conclusions: although sex, place of residence, occupation, and personal medical history were identified as risk factors related to COVID-19, information about the impact of other factors is still limited and requires further study.